Manajemen Strategi Gereja dalam Penginjilan Perkotaan - Deisy Agustina Tinangon; Beni Chandra Purba (PT. Penerbit Tiga Mutiara, 2024)
Evangelism is a command that comes directly from the mouth of Jesus Christ. The command to evangelize Matthew 28:19-20 was implemented by the Apostles in all places, both villages and cities. This is motivated by the command itself